(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Climate warming may lead to a strong transformation of many cryogenic geosystems of the world. High-mountain permafrost peat palsa-massifs having a relatively small area are particularly vulnerable. We studied four such massifs, the soils of which are diagnosed as Cryosols, within the Arabel Plateau of the Central Tien Shan. It is shown that a unique Ca-Fe geochemical landscape is formed on this territory, where active accumulation of carbonates in soils and micro-watersheds takes place. These landscapes actively participate in the formation of chemical runoff of rivers, and their function can change greatly in warmer climate.